ENTREPRENEURIAL PROFILES AMONG NATIVE STUDENTS FROM URBAN DAN RURAL SECONDARY SCHOOLS - Che Omar, Che Mohd Zulkifli; Baharudin, Aminah; Abdullah, Mohammad Khairudin Lim (International Business Education Journal, 2010)
The purpose of this study is to see how far entrepreneurial profiles among native students in urban and rural secondary schools. Besides that, this study also aims to observe whether there are any relationships in determining entrepreneurial profiles based on gender, school location, family background, residential area and field of studies. A total of 200 samples were chosen from eight secondary schools from urban and rural area in the district of Hilir Perak, Perak, Malaysia. A set of questionnaires containing 100 items was formulated to determine entrepreneurial profiles among native students from urban and rural secondary schools. Entrepreneurial profiles of native students were assessed using 13 competencies namely, (i) Initiative (ii) Looking and seeking for opportunities (iii) Tenacity (iv) Search for information (v) Emphasis on high achievement (vi) Committed towards work contract (vii) Orientation of proficiency (viii) To make systematic planning (ix) Ability of solving problem (x) Self confidency (xi) Certainty (xii) Able to convince others and (xiii) Able to use influencial strategy. In the study, two types of statitics were used namely descriptive and inferential statistics. Descriptive statistical analysis showed that native students possessed entrepreneurial profiles at the moderate level. This is proven where the mean scores were 3 for all competences. Therefore more effort to raise entrepreneurial profiles among natives students in secondary students should be done through curriculum and co-curiculum activities. T-test analysis was used to determine the difference in entrepreneurial profiles based on the variables. The findings showed there were no significant relationships among gender, school location, family background, residential area and field of studies in determining entrepreneurial profiles among native students in urban and rural secondary schools.